2010
DOI: 10.1007/s11300-010-0135-5
|View full text |Cite|
|
Sign up to set email alerts
|

The Money–Happiness Relationship in Transition Countries: Evidence from Albania

Abstract: Life satisfaction, Remittances, Subsidies, Transition countries, I30, C33, O15, P20,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…This literature has shown that, while relative income matters, positional effects do not fully crowd out the positive effect of personal income on individual well being. Furthermore, several studies have documented that an increase in the reference group income may become not necessarily bad news for individuals living (or perceiving to live) in socioeconomic environments characterized by high vertical mobility (Senik, 2004;Jiang et al, 2009;Becchetti and Savastano, 2009). The same literature has been extended to the role played by various inequality dimensions (income, weight) between partners and to that exerted by regional unemployment on the satisfaction of the unemployed (Clark, 2008 andClark et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This literature has shown that, while relative income matters, positional effects do not fully crowd out the positive effect of personal income on individual well being. Furthermore, several studies have documented that an increase in the reference group income may become not necessarily bad news for individuals living (or perceiving to live) in socioeconomic environments characterized by high vertical mobility (Senik, 2004;Jiang et al, 2009;Becchetti and Savastano, 2009). The same literature has been extended to the role played by various inequality dimensions (income, weight) between partners and to that exerted by regional unemployment on the satisfaction of the unemployed (Clark, 2008 andClark et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When doing so, we obviously control whether the country relative effect persists after controlling for various types of standard reference group effects 1 . Our findings provide additional insights on the well known treadmill effects and Easterlin paradox.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wealth also seems to play an important positive role in life satisfaction in transition economies. Namazie and Sanfey () find this relationship in a study of Kyrgyzstan, while Becchetti () uncovers it in a study of Albania.…”
Section: Literature Reviewmentioning
confidence: 94%
“…As a result, several studies have sought to identify characteristics associated with better or poorer tolerance of the economic and social changes brought by transition. For example, Becchetti () investigates the impact of money on happiness in Albania after transition and finds that the impact of money depends on the aspirations of the individual. Using survey data from three different years, beginning in early transition, Kalyuzhnova and Kambhampati () investigate the determinants of happiness in Kazakhstan, and find that dwelling size is positively associated with happiness and that ethnic Kazakhs are happier than Russians.…”
Section: Introductionmentioning
confidence: 99%